Farming on the edge: farmer attitudes to bovine tuberculosis in newly endemic areas. (31st October 2015) - Enticott, G.; Maye, D.; Carmody, P.; Naylor, R.; Ward, K.; Hinchliffe, S.; Wint, W.; Alexander, N.; Elgin, R.; Ashton, A.; Upton, P.; Nicholson, R.; et al.
Abstract : Defra's recent strategy to eradicate bovine tuberculosis (bTB) establishes three spatial zones: high‐risk areas (HRAs) and low‐risk areas, and an area referred to as 'the edge', which marks the areas where infection is spreading outwards from the HRA. Little is known about farmers in the edge area, their attitudes towards bTB and their farming practices. This paper examines farmers' practices and attitudes towards bTB in standardised epidemiologically defined areas. A survey was developed to collect data on farmer attitudes, behaviours, practices and environmental conditions as part of an interdisciplinary analysis of bTB risk factors. Survey items were developed from a literature review and focus groups with vets and farmers in different locations within the edge area. A case‐control sampling framework was adopted with farms sampled from areas identified as recently endemic for bTB. 347 farmers participated in the survey including 117 with bTB, representing a 70per cent response rate. Results show that farmers believe they are unable to do anything about bTB but are keen for the government intervention to help control the spread of bTB.